2008
DOI: 10.1099/vir.0.2008/000083-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of hepatitis C RNA-containing particles from human liver by density and size

Abstract: Hepatitis C virus (HCV) particles found in vivo are heterogeneous in density and size, but their detailed characterization has been restricted by the low titre of HCV in human serum. Previously, our group has found that HCV circulates in blood in association with very-low-density lipoprotein (VLDL). Our aim in this study was to characterize HCV RNA-containing membranes and particles in human liver by both density and size and to identify the subcellular compartment(s) where the association with VLDL occurs. HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 54 publications
1
50
0
1
Order By: Relevance
“…It was shown that silencing apoB and apoE or inhibiting microsomal triglyceride transfer protein activity abrogated HCV secretion. In earlier studies, apoE and apoB were found on the surface of infectious viral particles, suggesting that lipoproteins associate with viral particles to produce lipoviroprotein particles (51)(52)(53)(54). These findings raise the possibilities of viral entry via LDL or SR-B1 receptors, and indeed there have been studies that support this view (51,52,55,56).…”
Section: Discussionmentioning
confidence: 67%
“…It was shown that silencing apoB and apoE or inhibiting microsomal triglyceride transfer protein activity abrogated HCV secretion. In earlier studies, apoE and apoB were found on the surface of infectious viral particles, suggesting that lipoproteins associate with viral particles to produce lipoviroprotein particles (51)(52)(53)(54). These findings raise the possibilities of viral entry via LDL or SR-B1 receptors, and indeed there have been studies that support this view (51,52,55,56).…”
Section: Discussionmentioning
confidence: 67%
“…A hallmark of HCV infectious particles is their tight connection with very-low-density lipoproteins (VLDL) and low-density lipoproteins (LDL), giving rise to a hybrid form of lipoviral particles (LVPs) with heterogeneous buoyant density (5)(6)(7)(8)(9)(10)(11)(12). Nonexchangeable apolipoprotein B (apoB) and several exchangeable apolipoproteins (apoE, apoA-I, and apoC-I) have been found on the LVP surface (13)(14)(15).…”
mentioning
confidence: 99%
“…E1 could not be detected in the studied samples (data not shown), even though previous reports have described its presence in LVPs. 5,28 Symmetrically, envelope glycoprotein E2 was detected by a genotype 1a-specific monoclonal antibody in two LVP samples from 12 HCV genotype 1 patients (representative blot on Fig. 2C).…”
Section: Resultsmentioning
confidence: 98%
“…2,3 The most striking link between HCV and lipids resides in the association of HCV particles with lipoproteins. 4,5 Indeed, HCV virions with a density <1.06 g/mL are associated with lipoproteins, thus forming hybrid particles known as lipoviral particles (LVPs). These low-density viral particles are globular, rich in triacylglycerol and total cholesterol (TChol) and contain the viral envelope glycoproteins and nucleocapsid (composed of HCV RNA and core protein).…”
mentioning
confidence: 99%